Polymer composite materials : from macro, micro to nanoscale : selected, peer reviewed papers from the Conference on Multiphase Polymers and Polymer Composites Systems: Macro to Nano Scales, June 7-10, 2011, Paris, France - Boudenne, Abderrahim (Materials science forum ;, 2012)
The contents of this book pay particular attention to the different length-scales (macro, micro and nano) as related to obtaining a deeper understanding of the structure-property relationships of polymeric nanocomposite materials. They cover major findings and observations related to the morphological, interfacial, processing response, physical and thermophysical properties of multiphase polymers and polymer composite systems: from macro to nano length-scales. The presentation is organised around three areas: Multiscale modelling and simulation - Design and advanced characterisation - Processing, application and recycling.